Wide area robust TCSC controller design considering communication delay uncertainty - Saejia, Mongkol; Ngamroo, Issarachai (My University, 2010)
This paper focuses on a robust fixed structure controller design of thyristor controlled series capacitor (TCSC) for wide area stabilization taking uncertainty due to communication delay into account. Since the control signals measured from phasor measurement units (PMU) are global signals, the communication delay is an inevitable problem. When these PMU signals are used as the input of TCSC, the stabilization effect of TCSC may be deteriorated. To tackle this problem, an uncertainty due to time delay is represented by the inverse input multiplicative model. The structure of controller is the practical lead/lag compensator with single input. To enhance the robustness, the controller parameters are optimized by genetic algorithm (GA). Simulation studies in the two-area four-machine interconnected power system confirm the robustness of the proposed TCSC controller against the delay uncertainty.
Keywords: Robust control; Wide area stability control